2011
DOI: 10.1248/yakushi.131.1103
|View full text |Cite
|
Sign up to set email alerts
|

Anti-gastric Actions of Eugenol and Cinnamic Acid Isolated from Cinnamomi Ramulus

Abstract: We investigated the evidence of gastric protection for ulcer and gastritis by Cinnamomi Ramulus (Cinnamomum cassia Blume, Geiji, CR) extract and its several constituents. CR ethanolic extract showed the potent antioxidant activity and cytotoxicity of Helicobacter pylori (H. pylori) and acid-neutralizing capacity. Especially, eugenol exerted a signiˆcant antioxidant activity and inhibited the colonization of H. pylori. In vivo test, eugenol and cinnamic acid signiˆcantly inhibited HCl/ethanol-induced gastric le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 24 publications
2
25
2
Order By: Relevance
“…Among these, eugenol, gallic acid and ellagic acid, which are abundant constituents of SAWE, have antigastric effects and antioxidant activities (32)(33)(34). Based on the previous studies, the present study hypothesized that SAWE, which contains these bioactive components, has a preventive effect against gastric injury.…”
Section: Discussionmentioning
confidence: 80%
“…Among these, eugenol, gallic acid and ellagic acid, which are abundant constituents of SAWE, have antigastric effects and antioxidant activities (32)(33)(34). Based on the previous studies, the present study hypothesized that SAWE, which contains these bioactive components, has a preventive effect against gastric injury.…”
Section: Discussionmentioning
confidence: 80%
“…16) Ascorbic acid was used as a positive control. Anti-H. pylori Activity H. pylori strain (ATCC 43504) was obtained from ATCC (Rockville, MD, U.S.A.).…”
Section: Preparation Of Plant Extractmentioning
confidence: 99%
“…16) Thirty minutes after treatment, 1 mL of HCl-ethanol solution was administered orally for the induction of gastric lesions. After 1 h of fasting, each animal was sacrificed and the stomach was isolated.…”
Section: Preparation Of Plant Extractmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, several studies have reported that CR has various pharmacological activities such as vasodilatory (Kang & Shin, 2012), anti-inflammatory (Hwang et al, 2009), gastroprotective (Jung et al, 2011), anti-T2D (Suppapitipoen et al, 2006), and antioxidation (Dugoua et al, 2007;Lakshmi et al, 2009) effects. However, the mechanism of its antidiabetic activities has remained unclear.…”
Section: Introductionmentioning
confidence: 99%